2008
DOI: 10.1016/j.bbrc.2007.11.133
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calpain 10 activity and expression in the kidney of multiple species

Abstract: Calpains, Ca 2+ -activated cysteine proteases, have been implicated in the progression of multiple disease states. We recently identified calpain 10 as a mitochondrial calpain that is involved in Ca 2+ -induced mitochondrial dysfunction. The goals of this study were to characterize the expression and activity of renal mitochondrial calpain 10 in rabbit, mouse, and rat. Using shRNA technology and immunoblot analysis three previously postulated splice variants of calpain 10 were identified (50, 56, and 75 kDa). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…In other words, it is possible that calpain-3 may interact with RyR and/or triadin in the RyR-triadin-CSQ1 complex that spans the SR membrane. Alternatively, it is also possible that calpain-3 is located in the luminal SR, since other calpain members have been reported to exist in luminal compartments of organelles such as mitochondria 23,24,25,26. Further study is required to clarify the interaction of calpain-3 with CSQ1.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is possible that calpain-3 may interact with RyR and/or triadin in the RyR-triadin-CSQ1 complex that spans the SR membrane. Alternatively, it is also possible that calpain-3 is located in the luminal SR, since other calpain members have been reported to exist in luminal compartments of organelles such as mitochondria 23,24,25,26. Further study is required to clarify the interaction of calpain-3 with CSQ1.…”
Section: Discussionmentioning
confidence: 99%
“…In renal mitochondria, activation of mitochondrial calpain 10 impairs the electron transport chain by proteolytic digestion of complex I subunits [35,86]. Genetic ablation of complex I subunits sensitizes to the MPTP opening in mouse heart mitochondria [87].…”
Section: Mitochondrial Calpain 1 Within the Matrixmentioning
confidence: 99%
“…Calpain 10 is a ubiquitous calpain (30) and our laboratory showed that calpain 10 is resident in kidney mitochondria of rabbits, rats, and mice (4,16). Arrington et al (4) identified calpain 10 as a mitochondrial calpain capable of cleaving complex 1 proteins (ND6 and NDUFV2) and inhibiting state 3 respiration after mitochondrial Ca 2ϩ overload.…”
mentioning
confidence: 97%